2014
DOI: 10.1016/j.jsps.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate vs. resperidone in treatment of methamphetamine dependence: A clinical trial

Abstract: The present study confirmed that both methylphenidate and resperidone can successfully be used for treatment of MA dependence, in order to reduce drug craving and psychological, neurologic, and somatic problems in patients. However, the efficacy of methylphenidate was estimated to be less than that of resperidone for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Our results were in accordance with some previous studies [ 32 , 41 , 42 ]. Tiihonen and his colleagues have compared methylphenidate with aripiprazol for treatment of methamphetamine dependence, however, their study ended prematurely due to unexpected results of interim analysis and all of their patients were intravenous drug abuser; yet their results have been promising.…”
Section: Discussionsupporting
confidence: 94%
“…Our results were in accordance with some previous studies [ 32 , 41 , 42 ]. Tiihonen and his colleagues have compared methylphenidate with aripiprazol for treatment of methamphetamine dependence, however, their study ended prematurely due to unexpected results of interim analysis and all of their patients were intravenous drug abuser; yet their results have been promising.…”
Section: Discussionsupporting
confidence: 94%
“…In third trial the self-reported days of PWUM [ 55 ], but not in a fourth study [ 20 ]. In has been shown that the MPH at 10 mg/day is able to decrease the craving symptoms less than risperidone [ 19 ]. The primary pharmacologic effect of MPH is to enhance nor-epinephrine activity and dopamine, which impacts reward system function.…”
Section: Discussionmentioning
confidence: 99%
“…Tiihonen et al [ 18 ] showed the administration of 54 mg/day MPH compared with aripiprazole to patients with severe amphetamine dependence for 20 weeks led to a significant fewer amphetamine positive urine. Also, evidence studies have demonstrated that both risperidone and MPH can be useful for treatment of PWUM, in order to decrease the drug craving and somatic, psychological, and neurologic problems [ 19 ]. However, in another study, MPH administration was associated with no changes in the percentage of positive urines [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our search yielded 20 results, 11 of which did not meet inclusion criteria for this review [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Nine studies, including 242 participants met inclusion criteria (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%